GE_GERICHTE C/17162/2014 vom 24. Juni 2016 - GE Cour de justice (2016)
ACTION EN PAIEMENT D'ENTRETIEN ; QUALITÉ POUR AGIR ET RECOURIR ; OBLIGATION D'ENTRETIEN ; ENFANT ; COMPENSATIO ; ÉCOLE PRIVÉE | CC.277.2; CC.279; CC.304;